The essence and content characterization of the structural and functional components of the teacher’s communicative competence (Actual Problems of Psychology in Educational Institutions, 2020)
Abstract. This article analyses theoretical foundations of the problemof communicative competence as an integrative formation of a futureteacher’s personality. The variability of the definition of “communicativecompetence” was presented. The different scientists’ approaches to definingthe essence and content of the denoted phenomenon were considered.The basic structural and functional components of communicativecompetence (gnostic, motivational-value, operational-activity, reflexive,personal, emotional-volitional) and their substantive characteristics werespecified and defined. According to the results of theoretical analysis,communicative competence is defined as a system of internal reserves of apersonality necessary for communicative interpersonal interaction.
Keywords: competence; pedagogical competence; professional and pedagogical competence; communicative competence; functional and structural components